جهود الشيخ عبد الجبار في المؤسسات التعليمية في نشر التعليم الإسلامي شيتاغونغ 1933-1998م - Md Moslim Hider Madani; Robiatul Adawiyah Mohd @ Amat (Fakulti Pengajian Quran dan Sunnah, 2025)
E-Proceeding The9th International Conference on Nabawi Heritage(SWAN 2024) Theme: Prophetic Legacy in Development of Civil Society in the Era of Artificial Intelligence (AI) 6-7 November 2024